2017
DOI: 10.1007/s40732-017-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Delay, but not Probability Discounting, in Current Smokers, E-cigarette Users, and Never Smokers

Abstract: Steeper delay discounting in substance abuse populations, compared to non-abusing populations, has been well-established in prior studies. Despite the growing interest in e-cigarettes as a novel and relatively understudied form of nicotine consumption, relatively little is known as to how e-cigarette users discount rewards compared to traditional cigarette smokers and never smokers. In the present study, we measured delay and probability discounting rates, as well as perceived risk inherent to a delayed reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
1
18
2
Order By: Relevance
“…Several studies have shown that cigarette smokers discount delayed outcomes more steeply than nonsmokers for money (e.g., Bickel et al, 1999;Mitchell, 2004), food and entertainment (Friedel et al, 2014), and health (Friedel et al, 2016). Our data are consistent with these prior studies including previous work demonstrating that e-cigarette users discount money more than nonnicotine users (Białaszek et al, 2017). Importantly, we extended these differences between e-cigarette users and non-nicotine users to different nonmonetary outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies have shown that cigarette smokers discount delayed outcomes more steeply than nonsmokers for money (e.g., Bickel et al, 1999;Mitchell, 2004), food and entertainment (Friedel et al, 2014), and health (Friedel et al, 2016). Our data are consistent with these prior studies including previous work demonstrating that e-cigarette users discount money more than nonnicotine users (Białaszek et al, 2017). Importantly, we extended these differences between e-cigarette users and non-nicotine users to different nonmonetary outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Over the past decade, the tobacco product marketplace has become increasingly complex as the popularity of electronic cigarettes has grown (McMillen et al, 2014). Białaszek et al (2017) compared monetary delay discounting between cigarette smokers, e-cigarette users, and non-tobacco users. Cigarette smokers and e-cigarette users discounted similarly, and both groups showed steeper discounting than non-tobacco users.…”
mentioning
confidence: 99%
“…However, somewhat contrary to these data, Białaszek et al (2017) reported that EC users and cigarette smokers both differed significantly from, and approximately equally by visual comparison, a never-using control group. Here, we note that smokers in Bialaszek et al’s study showed minimal dependence (mean FTCD score: 2, or “very low” dependence; Fagerstrom et al, 1992).…”
Section: Discussioncontrasting
confidence: 69%
“…Because we were specifically interested in differences between individual EC and cigarette use subgroups to clarify prior mixed findings (Białaszek et al, 2017; Chivers et al, 2016; Weidberg et al, 2017), we also conducted planned pairwise comparisons of covariate-adjusted discount rates between individual subgroups. Sequential Bonferroni correction was used to maintain Type I error rate at the conventional level of α = .05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation